2019
DOI: 10.1186/s12889-019-7002-z
|View full text |Cite
|
Sign up to set email alerts
|

A population-based approach to integrated healthcare delivery: a scoping review of clinical care and public health collaboration

Abstract: Background A population-based approach to healthcare goes beyond the traditional biomedical model and addresses the importance of cross-sectoral collaboration in promoting health of communities. By establishing partnerships across primary care (PC) and public health (PH) sectors in particular, healthcare organizations can address local health needs of populations and improve health outcomes. The purpose of this study was to map a series of interventions from the empirical literature that facilitat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
79
0
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 65 publications
(82 citation statements)
references
References 59 publications
1
79
0
2
Order By: Relevance
“… 3 , 15 Regardless of setting, primary care has been encouraged to identify and account for the effects of exposure to high risk social and economic circumstances in vulnerable populations in order to better identify barriers to and facilitators of better clinical outcomes. 16 - 18 …”
Section: Discussionmentioning
confidence: 99%
“… 3 , 15 Regardless of setting, primary care has been encouraged to identify and account for the effects of exposure to high risk social and economic circumstances in vulnerable populations in order to better identify barriers to and facilitators of better clinical outcomes. 16 - 18 …”
Section: Discussionmentioning
confidence: 99%
“…Researchers should consider studying the arts and the prevention of SUD using a population-based approach. A population health approach focuses on the health and overall wellness of broader populations (e.g., communities, neighborhoods, cities, states, nations) rather than providing acute care to individual patients (Shahzad et al, 2019). Some population-based research suggests a positive relationship between self-reported arts engagement and health.…”
Section: Research Question 2: What Is the Evidence On The Role Of The Arts In The Prevention Of Sud Including Oud?mentioning
confidence: 99%
“…), diagnosis and treatment of communicable diseases, prevention and control of non-communicable diseases (NCD), maternal and neonatal care, tobacco control, violence prevention, and food safety. 11 The Department of Health Budget Report in 2018 indicated that based on the continuum of care, preventive and promotive healthcare had the highest share of funds (38%, PhP 40.75B) which included health promotion, HRH deployment, and public health management. A significant portion (50%, PhP 53.07B) went to curative health care which included operations and upgrading of DOH and local government hospitals (Figure 1).…”
Section: Resources Needed To Deliver Population-based Health Servicesmentioning
confidence: 99%
“…To improve accessibility and quality in healthcare, patient navigators should also be engaged in the health system. 11,12 The discussion also emphasized the distinction between the source of health funds based on the current law and the UHC law which are facility-based and network-based, respectively. As the UHC law implements a networkbased trust fund, private health providers will need to join networks to adapt to the new health system.…”
Section: Weaknesses Of the Current Sdnsmentioning
confidence: 99%